2003
DOI: 10.1152/jn.00697.2002
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Brain Stem Gap Junctions Increases Phrenic Burst Frequency and Reduces Phrenic Burst Synchronization in Adult Rat

Abstract: Recent investigations have examined the influence of gap junctional communication on generation and modulation of respiratory rhythm and inspiratory motoneuron synchronization in vitro using transverse medullary slice and en bloc brain stem-spinal cord preparations obtained from neonatal (1–5 days postnatal) mice. Gap junction proteins, however, have been identified in both neurons and glia in brain stem regions implicated in respiratory control in both neonatal and adult rodents. Here, we used an in vitro art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 53 publications
5
41
0
Order By: Relevance
“…Two putative gap junction blockers which have been used widely in the assessment of syncytial function are the alkanol, 1-heptanol, and the hydroxysteroid dehydrogenase inhibitor, carbenoxolone. Recent reports have suggested that carbenoxolone over a concentration range of 10-200 μM blocks gap junctions more selectively than does heptanol , which has been suggested to have non-specific actions on ionic channels (Margineanu and Klitgaard, 2001;Solomon et al, 2003). In the present study we find, in the smooth muscle of GPVD, that the effects of carbenoxolone are indeed more consistent with gap junction block than are those of heptanol.…”
Section: Discussionsupporting
confidence: 70%
“…Two putative gap junction blockers which have been used widely in the assessment of syncytial function are the alkanol, 1-heptanol, and the hydroxysteroid dehydrogenase inhibitor, carbenoxolone. Recent reports have suggested that carbenoxolone over a concentration range of 10-200 μM blocks gap junctions more selectively than does heptanol , which has been suggested to have non-specific actions on ionic channels (Margineanu and Klitgaard, 2001;Solomon et al, 2003). In the present study we find, in the smooth muscle of GPVD, that the effects of carbenoxolone are indeed more consistent with gap junction block than are those of heptanol.…”
Section: Discussionsupporting
confidence: 70%
“…The phrenic discharge data used for this study were obtained in our previous experiments conducted in an in vitro arterially-perfused decerebrate adult rat (81-125g, ~5-6 wk old; n=10) preparation [4].…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
“…Two prominent peaks in the PSD, referred to as medium and high frequency oscillations (MFO and HFO, respectively), have been identified, and they are believed to represent synchronization of inspiratory neuronal activities [1,3,4]. We have recently developed a 9 parameter mathematical model that is capable of characterizing the major spectral features associated with these inspiratory-phase fast oscillations [5].…”
Section: Introductionmentioning
confidence: 99%
“…GZA is a congener of carbenoxolone, and it has been used as a control substance to test for nonspecific effects of carbenoxolone (46,63). We studied the effect of unilateral perfusion of GZA in the RTN on ventilatory responses to CO 2 in five animals (mean age 10.2 Ϯ 0.9 wk).…”
Section: Ventilatory Effects Of Unilateral Acidification Of Rtn With mentioning
confidence: 99%
“…Immunohistochemical staining demonstrated the presence of Cx26, Cx32, and Cx36 in multiple regions of the brain stem involved in respiratory control (62,64). Of the respiratory-related sites in which gap junctions are expressed, the pre-Bötzinger complex, locus ceruleus (LC), retrotrapezoid nucleus (RTN) in the ventrolateral medulla, and nucleus of the solitary tract (NTS) are sensitive to CO 2 (9,44,63). Therefore, gap junctions may be a necessary component of central CO 2 chemosensitivity (12).…”
mentioning
confidence: 99%